Teaching Language Learning Strategies - Anna Uhl Chamot (Asociación Colombiana de Profesores de Ingles, 2016)
What is a learning strategy? "Learning strategies are special ways of processing information that enhance comprehension, learning, or retention of the information" (O'Malley & Chamot, 1990, p. 1).